Barrier property enhancement of starch citrate bioplastic film by an ammonium-thiourea complex modification - O.D. Saliu; G.A. Olatunji; A.I. Olosho; A.G. Adeniyi; Y. Azeh; F.T. Samo; D.O. Adebayo; O.O. Ajetomobi (Journal of Saudi Chemical Society)
Although citric acid modification of starch biopolymers gives a more thermodynamically stable starch citrate, the barrier properties of the product is relatively poor. This paper reports a novel modification process which significantly improved the barrier properties of starch citrate by treating it with a complex formed from ammonium acetate and thiourea in the presence of a polysorbate catalyst. The barrier characteristics which were investigated include percentage moisture absorption, percentage reflectance, and water vapour release study. FTIR, SEM and TGA were employed to characterize the starch citrate biofilms before and after ammonium-thiourea complex modifications. Keywords: Bioplastics, Starch citrate, Barrier properties, Thiourea, Biopolymers